“THE LION ON THE PATH AND OTHER AFRICAN STORIES”, told by Hugh Tracey. Illustrated by Eric Byrd. Music transcribed by Andrew Tracey. London, Routledge and Kegan Paul. 1967. 18/- 127 pp. - Dey, E. (International Library of African Music, 1968)
pages: 65
Keywords: African Music